Norwegian PhD students' discourses about practice‐relevant research in the field of health and social work - Margareth Kristoffersen; Åse Vagli; Bjørg Frøysland Oftedal (Wiley, 2020)
Abstract Aim The aim of this study was to explore the discourses of PhD students concerning the performance of practice‐relevant research in health and social work. Design An explorative, qualitative design and a discourse analytical approach were used to collect data. Methods Participants were recruited from a national research school for practice‐relevant research in Norway. Group interviews with ten PhD students (five health and five social work professionals) with extensive, wide‐ranging work experience as practitioners were used to collect data. The data were analysed by discourse analysis. Results The analysis revealed three discourses: (a) the professional knowledge discourse; (b) the promoting partnership discourse; and (c) the using research knowledge discourse. The discourses are explicit concerning how systematically formed practice‐relevant research in health and social work is linked to dominant discourses about knowledge in the scientific field. Professional knowledge, promoting partnership and using research knowledge are fundamental features of practice‐relevant research.